Flapless Root Resection of Both Maxillary First Molars’ Distobuccal Root: Case Report - Hatice Balci Yüce; Feyza Tülü; Fatma Uçan Yarkaç (Journal of Dentistry And Oral Implants, 2017)
Background: Furcation involvement is characterized by periodontal disease invading furcation regions of multi-rooted teeth. Treatment modalities are scaling and root planning and surgical management such as osteoplasty or ostectomy, odontoplasty, bicuspidization, root resection and hemisection. Periodontally compromised maxillary molars generally have poor prognosis because of inter radicular loss of attachment, and difficulty in access and treatment. Root resection is procedure by which one or more of the roots of a tooth are removed at level of furcation while leaving crown and the remaining roots in function. Case: A 58 year-old female patient applied to Periodontology clinic with complaints of sensibility and gingival recession in teeth number 16 and 26. Both teeth were completely exposed due to severe attachment loss in distobuccal root. There was also second degree mobility on the right molar and third degree mobility on the left molar teeth. Flapless root resection were planned after root canal therapy. After local anesthesia, distobucal roots were resected by high speed rotary motor with adequate irrigation at the level of the furcation roof. A small cavity was prepared and retrograded with glass ionomer cement. A platelet-rich fibrin membrane was obtained from patient’s blood and stitched to the distal surface of right first molar. Left first molar area was left uncovered. Recovery was followed on 2nd, 8th week and 6th month. When healing was compared between left and right sides, no mobility was observed and a slight redness and swelling was observed on the right side at 2nd week. At 8th week, there was no difference in clinical appearance. At 6th month, all complaints of the patient were gone and prognosis of the teeth was good.
Keywords: Furcation defect